Structural Design and Position Analysis of Parallel Leg of Hexapod Agriculture Robot - Xie Dongfu; Luo Yufeng; Shi Zhixin; Liu Yande (Jixie chuandong)
A parallel leg mechanism of hexapod agricultural robot with 1 translation and 2 rotation (1T2R) is designed and studied based on the theory of direction and position characteristics ( POC). Firstly, based on the method of POC, a number of parallel leg mechanisms satisfying the functional requirements are synthesized. Then, according to the actual needs of agricultural application, a mechanism with superior performance is selected. The analysis results show that the mechanism has the advantages of simple structure, large workspace and convenient control. Finally, the position forward and inverse solutions of the optimized mechanism are analyzed. The results show that the forward and inverse solutions of the mechanism are simple, both of them can be solved analytically, and the forward and inverse solutions of the mechanism have at most four sets of solutions.